PLACE OF CARE TOWARDS THE END OF LIFE IN CHILDREN AND YOUNG PEOPLE WITH LIFE-THREATENING AND LIFE-LIMITING CONDITIONS: A LITERATURE REVIEW. Issue 1 (1st March 2013) - Beecham, E; Kelly, P; Candy, B; Jones, L; Bluebond-Langner, M
Abstract : Introduction: The UK palliative care funding review is examining use and costs of palliative care services (PCS) including provision of end of life (EoL) care for children and young people (CYP) with life-limiting and life-threatening conditions (LL/LTC). Current provision is funded through a range of statutory and voluntary organisations. Place of care (POC) towards EoL may be influenced by several factors including service availability, attitudes of health and social care professionals, and patient and family-centred issues. Aims and Methods: We sought to review the current evidence on POC in CYP with LL/LTC towards the EoL. An initial search was conducted in January 2011 (currently being updated) of databases MEDLINE, EMBASE and CINAHL. We included empirical peer reviewed papers published between 2004–2011 with data on POC for CYP towards the EoL. Results: To date 28 papers meet review inclusion criteria. Study quality is variable. We found evidence that CYP with Leukaemia, Lymphoma, and Cystic Fibrosis, those from ethnic minorities and those aged less than 1 year were more likely to die in hospital. CYP with solid tumours, those aged more than 1 year and those of male gender were more likely to die at home. Explanations for POC were poorly evidenced; most studies cited availability/access of services but few explored issues underlying preferences for POC. Conclusions: Knowledge and understanding of factors affecting POC for CYP towards EoL is limited. Robust data are required to inform PCS provision and ensure that funding is available for care in appropriate locations to meet CYP clinical needs and family preferences.